The Influence of Ethical Leadership, Affective Commitment, Knowledge Sharing, Innovation Climate, and Technology Acceptance on Innovative Behavior of Secondary ART Teachers in SPK Schools in Jakarta - Roma Eka Vanesha Maryanto; Ardi Kho (Jurnal Sosial Teknologi, 2026)
This research investigates the structural determinants of Art Teachers’ Innovative Behavior (ATIB) in Indonesian SPK (international-curriculum) secondary schools using Partial Least Squares Structural Equation Modeling (PLS-SEM). Grounded in ethical leadership, affective commitment, knowledge sharing, organizational innovation climate, and technology acceptance frameworks, the study examines how leadership- and technology-related factors influence innovative behavior. Data were collected from 97 secondary art teachers implementing Cambridge IGCSE, Pearson Edexcel GCSE, and IB MYP Visual Arts curricula. The results indicate that Technology Acceptance is the strongest predictor of ATIB (β = 0.496, p < 0.001), followed by Knowledge Sharing (β = 0.243, p = 0.020) and Organizational Innovation Climate (β = 0.208, p = 0.019). Ethical Leadership and Affective Commitment do not significantly predict innovative behavior, and Knowledge Sharing does not mediate these relationships. The structural model explains 61.1% of the variance in ATIB. These findings suggest that within standardized and digitally integrated international-school environments, innovation is driven more by technological readiness and collaborative systems than by leadership ethics alone, highlighting the critical role of digital integration in contemporary art education contexts.